Violent Radicalisation Prevention in Northern Nigeria: The Socio-Economic Roles of Religious Leaders - Obiwuru, Rex (Journal for deradicalization, 2025)
Violent extremism remains one of the biggest security challenges in northern Nigeria. This study takes a grassroots approach, particularly investigating how religious leaders address the socio-economic factors that render people vulnerable to violent radicalisation in that region. Data for the study were generated from ten qualitative interviews with Christian and Muslim leaders across five locations in the region. Thematic analysis was then applied to identify and interpret key themes within the perspectives and experiences shared by the participants. It pioneers the application of the faith-based humanitarianism (FBH) concept to the study of violent radicalisation prevention and argues that religious leaders are more than just theological authorities; they are also practical socio-economic agents of prevent. It finds that they use their influence and network to facilitate individual and communal resilience, critical thinking, and social and economic empowerment in vulnerable communities. It concludes by suggesting that their contributions may play an important role in the prevention of violent radicalisation, especially in Nigeria’s northern region, where issues of poverty, unemployment, and lack of education increase radicalisation risks.